Cationic lipid-based formulations for encapsulation and delivery of anti-EFG1 2'OMethylRNA oligomer - Araújo, Daniela Eira (2022)
The effective protection and delivery of antisense oligomers to its site of action is a challenge without an optimal strategy. Some of the most promising approaches encompass the complexation of nucleic acids, which are anionic, with liposomes of fixed or ionizable cationic charge. Thus, the main purpose of this work was to study the complexation of cationic liposomes with anti-EFG1 2′OMe oligomers and evaluate the complex efficacy to control Candida albicans filamentation in vitro and in vivo using a Galleria mellonella model. To accomplish this, cationic dioleoyl-trimethylammoniumpropane (DOTAP) was mixed with three different neutral lipids dioleoyl-phosphocholine (DOPC), dioleoyl-phosphatidylethanolamine (DOPE) and monoolein (MO) and used as delivery vectors. Fluorescence Cross Correlation Spectroscopy measurements revealed a high association between antisense oligomers (ASO) and cationic liposomes confirming the formation of lipoplexes. In vitro, all cationic liposome-ASO complexes were able to release the anti-EFG1 2′OMe oligomers and consequently inhibit C. albicans filamentation up to 60% after 72 h. In vivo, from all formulations the DOTAP/DOPC 80/20 ρchg = 3 formulation proved to be the most effective, enhancing the G. mellonella survival by 40% within 48 h and by 25% after 72 h of infection. In this sense, our findings show that DOTAP-based lipoplexes are very good candidates for nano-carriers of anti-EFG1 2′OMe oligomers.